The labor market impact of a taxi driver's license - Mounir Karadja; Anton Sundberg (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
We study the economic impact of becoming a taxi driver. Comparing individuals who pass the necessary written exams for a taxi driver's license to individuals who have not yet done so, we find that both immigrants and natives who enter into taxi driving have experienced negative employment trends. However, after passing the written taxi exams, immigrants increase their monthly earnings by nearly 50 percent between 1 and 3 years later, and usage of social insurance programs decreases as well. For natives, we find positive but much smaller effects of passing taxi exams, which are large enough for their post-taxi earnings to be roughly 10 percent larger. An analysis of heterogeneous effects shows that effects are larger for recently arrived immigrants. We also find evidence in favor of immigrants having poorer outside options in the labor market, which may be a reason for their larger earnings impact of taxi driving compared to natives.
Keywords: J15; J22; J24; J60; J61; 330; Taxi labor market; Driver's licenses; Immigrant-native earnings gaps